2016
DOI: 10.1002/ajmg.b.32446
|View full text |Cite
|
Sign up to set email alerts
|

Pathway analysis in attention deficit hyperactivity disorder: An ensemble approach

Abstract: Despite a wealth of evidence for the role of genetics in attention deficit hyperactivity disorder (ADHD), specific and definitive genetic mechanisms have not been identified. Pathway analyses, a subset of gene-set analyses, extend the knowledge gained from genome-wide association studies (GWAS) by providing functional context for genetic associations. However, there are numerous methods for association testing of gene sets and no real consensus regarding the best approach. The present study applied six pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 73 publications
2
29
0
1
Order By: Relevance
“…Animal studies have shown that it acts as a ligand for PlexinA1, which is involved in critical steps of neuronal development in the spinal cord 29 and cardiac development 30,31 . This finding is consistent with prior research implicating neurite outgrowth dysregulation in ADHD 24,32 , and highlighting it as potential neural mediator of genetic risk for ADHD. This should be tested in future studies by applying imaging genetics mediation models 33 or Mendelian randomization approaches 34 .…”
Section: Discussionsupporting
confidence: 91%
“…Animal studies have shown that it acts as a ligand for PlexinA1, which is involved in critical steps of neuronal development in the spinal cord 29 and cardiac development 30,31 . This finding is consistent with prior research implicating neurite outgrowth dysregulation in ADHD 24,32 , and highlighting it as potential neural mediator of genetic risk for ADHD. This should be tested in future studies by applying imaging genetics mediation models 33 or Mendelian randomization approaches 34 .…”
Section: Discussionsupporting
confidence: 91%
“…Examination of the "molecular landscape" derived from the top findings from these initial GWAS studies along with other data concluded that genes regulating directed neurite outgrowth were strongly implicated in the etiology of ADHD [90]. Pathway and gene set analyses of GWAS data implicated pathways involved in the regulation of neurotransmitter release, neurite outgrowth and axon guidance as contributors to the etiology of ADHD [91][92][93].…”
Section: Genome-wide Significant Common Variantsmentioning
confidence: 99%
“…It is well‐known that ADHD has a strong genetic loading as shown by several studies reporting increased ADHD rates and co‐morbid psychiatric symptoms in ADHD children's parents in comparison with healthy controls (Okan Ibiloglu et al., ). Genetic ADHD background has been only partially explored: recent pathway analyses demonstrated that different mechanisms are involved in the pathogenesis of ADHD including neurotransmitter release dysregulation, and abnormalities in neurite outgrowth and axon guidance (Mooney, McWeeney, Faraone, Hinney & Hebebrand, ). As well as genetics, it is well‐known that some environmental habits, such as smoking during pregnancy, alcohol consumption and lead exposure all increase the risk of ADHD onset (Jaspers et al., ; Koshy, Delpisheh & Brabin, ; Melchior et al., ; Pineda et al., ).…”
Section: Introductionmentioning
confidence: 99%